[(-3)+9] × [(-10)-(-9)]
6 × (-10 + 9)
6 × (-1)
= -6
Answer:
Step-by-step explanation:
= 7(19) - 142(31) = <em>- 4269</em>
= 7(- 8)(- 9) + 11(2)(- 16) + 21(55)(- 1) - 21(- 8)(- 16) - 7(2)(- 1) - 11(55)(- 9) = <em>1768</em>
= 9.07(2.5)(2.35) + 6.02(3.5)(3.55) + 2.01(- 30.7)(- 1.1) - 2.01(2.5)(3.55) - 9.07(3.5)(- 1.1) - 6.02(- 30.7)(2.35) = <em>647.3561</em>
Answer:
Step-by-step explanation:
Answer:A= minimum value
B=lower quartile
C=median
D= upper quartile
E= maxuim value
Step-by-step explanation:
I would say the correct answer is B
I might be wrong